The Enteric Nervous System in Inflammation and Pain: The Role of Proteinase-Activated Receptors - Nathalie Vergnolle (Canadian Journal of Gastroenterology)
The enteric nervous system (ENS) plays a pivotal role in inflammatory and nociceptive processes. Drugs that interact with the ENS have recently raised considerable interest because of their capacity to regulate numerous aspects of the gut physiology and pathophysiology. The present article summarizes recent research on proteinases and proteinase-activated receptors (PARs) as signalling molecules in the ENS. In particular, experiments in animal models suggest that PAR2 is important to neurogenic inflammation in the intestine. Moreover, PAR2 agonists seem to induce intestinal hypersensitivity and hyperalgesic states, suggesting a role for this receptor in visceral pain perception. Thus, PARs, together with the proteinases that activate them, represent exciting new targets for therapeutic intervention on the ENS.